2016
DOI: 10.1080/15592294.2016.1252891
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes as prognostic predictors in endometrial carcinomas

Abstract: Endometrial carcinoma is one of the most frequent gynecological malignancies of the female. The diagnostic and prognostic markers for the high-risk subgroups with unfavorable prognosis are under intense debate worldwide, and, therefore, the aim of this study was to identify new potential DNA methylation markers for the high-risk groups. We used the Illumina Infinium HumanMethylation450 BeadChip to analyze the DNA methylation pattern and investigated its association with clinicopathological features important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Overall, few studies have evaluated the potential predictive role of DNA methylation patterns in EC prognosis. Although TBX2, CHST11, and NID2 were identified as having specific DNA methylation signatures for unfavorable clinical predictive and prognostic factors and a prognostic model that contained 15 methylation markers was recently established to distinguish EC patients with a poorer prognosis 18,19 biomarkers with higher accuracy should be investigated to assist in prognosis prediction for EC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, few studies have evaluated the potential predictive role of DNA methylation patterns in EC prognosis. Although TBX2, CHST11, and NID2 were identified as having specific DNA methylation signatures for unfavorable clinical predictive and prognostic factors and a prognostic model that contained 15 methylation markers was recently established to distinguish EC patients with a poorer prognosis 18,19 biomarkers with higher accuracy should be investigated to assist in prognosis prediction for EC patients.…”
Section: Discussionmentioning
confidence: 99%
“…During recent decades, a few specific DNA methylation signatures associated with high-risk EC and a series of altered methylation genes associated with unfavorable prognostic factors have been identified, such as TBX2, CHST11, PTEN and NID2 1820 . Even though advanced studies permit genome-wide screening at the DNA methylation or mRNA expression level, the mechanisms of DNA methylation that are involved in the regulation of gene expression and affect prognosis in EC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, combination of any two genes increased sensitivity to 91.8% with 95.5% specificity [30]. Another study identified an association between poor prognostic factors in high-risk (grade three) tumours and genes TBX2, CHST11 and NID2 [31].…”
Section: Dna Methylationmentioning
confidence: 99%
“…On the other hand, TBX2 inhibits cell cycle progression in lung adenocarcinoma (15) and its expression is decreased in lung cancers compared to normal tissue (16). Furthermore, TBX2 methylation has been associated with a poor prognosis in chronic lymphocytic leukemia (17), endometrial cancer (18) and bladder cancer (19). Thus, TBX2 may also exert an anti-tumor activity depending on the context and cellular origin of cancers.…”
Section: Dna Demethylation Agent 5azadc Downregulates Hpv16 E6 Expresmentioning
confidence: 99%